2013
DOI: 10.1037/a0030873
|View full text |Cite
|
Sign up to set email alerts
|

Comparing growth trajectories of risk behaviors from late adolescence through young adulthood: An accelerated design.

Abstract: Risk behaviors such as substance use or deviance are often limited to the early stages of the life course. Whereas the onset of risk behavior is well studied, less is currently known about the decline and timing of cessation of risk behaviors of different domains during young adulthood. Prevalence and longitudinal developmental patterning of alcohol use, drinking to the point of drunkenness, smoking, cannabis use, deviance, and HIV-related sexual risk behavior were compared in a Swiss community sample (N = 2,8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 34 publications
(51 reference statements)
3
32
0
Order By: Relevance
“…Research suggests that rates of cigarette use, HED, and marijuana use rise through the early 20s and subsequently decline for all subgroups similarly (Chen & Kandel, 1995; Brobeck, Bachmann, Croudace, & Brown, 2013; Lee, Mun, White, & Rutgers, 2010), suggesting gender and racial/ethnic disparities in use are relatively stable throughout adolescence and young adulthood. Other research suggests existence of a crossover effect, such that Hispanic and Black adolescents have lower rates in adolescence but higher rates later in adulthood (French, Finkbiner, & Duhamel, 2002; Geronimus, Neidert, & Bound, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Research suggests that rates of cigarette use, HED, and marijuana use rise through the early 20s and subsequently decline for all subgroups similarly (Chen & Kandel, 1995; Brobeck, Bachmann, Croudace, & Brown, 2013; Lee, Mun, White, & Rutgers, 2010), suggesting gender and racial/ethnic disparities in use are relatively stable throughout adolescence and young adulthood. Other research suggests existence of a crossover effect, such that Hispanic and Black adolescents have lower rates in adolescence but higher rates later in adulthood (French, Finkbiner, & Duhamel, 2002; Geronimus, Neidert, & Bound, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have even documented connections between transition to adulthood functioning and important life outcomes observed 25 years later (Johnson, Galambos, & Krahn, 2014). Specific to alcohol consumption, prior research identified a pattern of increasing alcohol consumption from late adolescence through the transition to adulthood, followed by subsequent declines in consumption as the transition to adulthood draws to a close and through young adulthood, a pattern that is likely due to changes in independence and responsibilities around this life period (Brodbeck, Bachmann, Croudace, & Brown, 2013;Schulenberg & Zarrett, 2006). Increased independence and autonomy from parents, coupled with few fullfledged adult responsibilities, allows for more freedom to engage in potentially risky behaviors, such as consuming alcohol and engaging in one-time sexual encounters, than any other period in the life span.…”
Section: Alcohol Use Binge Drinking and Drunkennessmentioning
confidence: 94%
“…Recent neuroimaging studies in adolescents between 11 and 19 years of age have confirmed that, when observed by peers, young adolescents show a weaker activation of brain areas associated with cognitive control and instead show higher neuronal activity in regions associated with rewards, which explains the youngsters' need to actively seek acceptance of their social group (Brodbeck et al, 2013;Chein et al, 2011;Guyer et al, 2014;Steinberg, 2008). The phenomenon of regulatory difficulty before social stimuli has also proved to be associated with a higher occurrence in risk behaviors such as substance use, and risky sex behaviors, among others (Brodbeck et al, 2013;Chein et al, 2011;Guyer et al, 2014;Steinberg, 2008). …”
Section: -8 Yearsmentioning
confidence: 95%
“…The time gap between 11 and 13 years of age is considered critical for the development of ER skills. Research in this field has registered how young adolescents spend lots of their time thinking about how they are perceived by others and concerned about their status in their social group (Chein et al, 2011;Brodbeck, Bachmann, Croudace, & Brown, 2013;Brodbeck et al, 2013;Silk et al, 2003;Steinberg, 2008;Zeman et al, 2006). It is also well documented how social circumstances, specifically the presence of peers, place high levels of stress and highly emotional arousal among young adolescents, and situations that expose them to the possibility of being negatively evaluated by their peers cause a considerable decrease in their self-regulatory capacity, lower assertiveness and limited decision-making strategies (Garnefski & Kraaij, 2006;Guyer et Emotion Regulation in Children and Adolescents:…”
Section: -8 Yearsmentioning
confidence: 99%